Changing Trend of Instrumental Vaginal Deliveries at Patan Hospital - Lamichhane, B; Singh, A (Nepal Journal of Obstetrics and Gynaecology, 2016)
Aims: The aim of the study was to evaluate the changing trend of the instrumental vaginal deliveries at Patan hospital over the last 10 years. Methods: This was a retrospective study done at Patan hospital. The study included data of 10 years duration (July 15th, 2004 – July 14th, 2014). The data included total normal delivery, caesarean section, vacuum delivery, forceps delivery and total delivery of the respective years. Results: Out of 80,149 deliveries over 10 years, 1635 (2.03%) were instrumental vaginal delivery (IVD). The study revealed progressive decline in overall trend of instrumental vaginal delivery. The highest percentage of IVD in the year 2005 was 265 (16.02%) and tangential dropped to 49 (2.9%) by 2014. The study revealed markedly decreased trend in vacuum delivery from 2005 to 2010, but a positive deflection was noticed till 2013, and abrupt fall in the year 2014.Regarding forceps delivery, a gradual fall in trend was noticed over the years. Over the last 10 years the mean percentile value of vacuum delivery was 78.47% while that of forceps was 21.52 %. Conclusions: The trend of instrumental vaginal delivery has markedly declined. On the other hand, it has shown increasing trend in caesarean delivery.